Vision based optical manipulation of biological cell with unknown trapping stiffness - Li, Xiang (2016)
Current robotic manipulation techniques for optical tweezers assume that the trapping stiffness of optical trap is constant and exactly known. In addition, the dynamic interaction between the cell and the manipulator of laser source is usually ignored in the analysis of the optical manipulation problem. In this paper, a control scheme is proposed for optical manipulation of biological cell with unknown trapping stiffness, which allows the laser beam to automatically trap and manipulate the cell to a desired position. The requirement on the model of the trapping stiffness is eliminated in the proposed formulation and thus system identification and calibration are not needed. The stability of the overall system is analyzed by using Lyapunov-like method, with consideration of the dynamics of both the cell and the manipulator of laser source. Experimental results are presented to illustrate the performance of the proposed cell manipulation method.